Persuasive technology from Islamic perspective - Bawazir, Mohammed Abdullah; Mahmud, Murni; Abdul Molok, Nurul Nuha (Institute of Electrical and Electronics Engineers Inc., 2018)
The effective use of persuasive technology in health, computing, sales, education, environment, etc is rapidly expanding. Persuasive technology is efficient in changing the attitudes and behaviours of end users. This paper demonstrates how persuasive technology and its design factors proposed in FBM are associated with the Islamic perspective from the Quran and Hadith. This paper starts by explaining the ethics of persuasive technology and discussing persuasive technology and its principal design factors in the Islamic perspective. The paper also discusses the extent to which Islamic principles enhance the concept of persuasive technology as an interactive computing system that could change attitudes and behaviours. In particular, this paper discusses how practices and principles of the design factors of persuasive technology were identified and applied in early Islamic era. The conceptual findings assert that Islamic principles are a universal and contemporary religion that cares for persuasive technology concepts.